1976
DOI: 10.1056/nejm197604082941505
|View full text |Cite
|
Sign up to set email alerts
|

Violence, Television and the Health of American Youth

Abstract: In 1973, 18,032 young Americans, 15 to 24 years of age, died in motor-vehicle accidents, 5182 were murdered, and 4098 committed suicide. The death rate, for this age group, was 19 per cent higher in 1973-74 than it had been in 1960-61, owing entirely to deaths by violence. The largest rise in deaths from homicide during the past two decades was at the ages of one to four. For a considerable proportion of American children and youth, the "culture of violence" is now both a major health threat and a way of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
6

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 4 publications
0
7
0
6
Order By: Relevance
“…Television has been postulated to cause an increase in violence, paranoia, and hyperactivity in children (202,203). Since there may be no educational source as all pervasive as TV, continued studies of its effect on behavior and physical health is mandatory.…”
Section: Behavior and Related Areasmentioning
confidence: 99%
“…Television has been postulated to cause an increase in violence, paranoia, and hyperactivity in children (202,203). Since there may be no educational source as all pervasive as TV, continued studies of its effect on behavior and physical health is mandatory.…”
Section: Behavior and Related Areasmentioning
confidence: 99%
“…Often reviews have drawn strong inferences from studies they believe to show an activation effect. On the basis of these studies, some people have condemned the broadcasters and have suggested remedial action (Bandura, 1973;Liebert, et al, 1973;Rothenberg, 1975; Sommers, 1976). Some of the studies cited by these reviewers, however, show only minimal effects and some studies showing no effects have been ignored.…”
Section: Strong Inferences From Weak Effectsmentioning
confidence: 99%
“…Some previous reviews on this topic have supported the view that T V violence is a significant cause of aggressive behavior (Bandura, 1973;Comstock, 1975;Liebert, Neale, & Davidson, 1973;Murray, 1973). On the basis of these reviews, there have been calls for restrictions on the broadcasting of televised fantasy violence (Rothenberg, 1975;Sommers, 1976) and there is evidence that such positions have affected broadcast policy (Carter & St rickland, 1975). It is our argument here that the evidence that TV causes aggression is not strong enough to justify restrictions in programming.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…American society, it is argued, is fed a continual mixture of real and imagined violence either through news documentaries or from "drama". This communicates, to children in particular, the idea that violent means are appropriate for resolving conflicts (Leading Article, 1976;Rotherberg, 1975;Somers, 1976;Inglefinger, 1976).…”
mentioning
confidence: 99%